Leadership and Work Engagement of staff nurses: A Systematic Review - Buchakun, Chutikarn; Singchungchai , Phechnoy; Chatdokmaiprai, Kannikar (Journal of The Royal Thai Army Nurses, 2020)
The purposes of this research study were to analyze the theories of leadership and work engagement of nursing personnel, and to synthesize empirical evidence about leadership and work engagement. The samples were 24 research reports, which were selected according to the specified criteria. The Research instruments was the Quality Assessment Criteria for Research Papers. The instrument quality was evaluated by using Kappa statistics to test the consistency between assessors in the research team. The findings of the research study showed that the transformational leadership theory is the most using leadership theory in research studies (n = 12), which is an independent variable (n = 24). For work engagement of registered nurse used three dimension measurement was primarily used (n = 23), namely vigor, dedication, and absorption. The greatest number of reports in correspondence to the leadership theories were found from 2015 to 2019 (n = 17), The data were collected by using a questionnaire (n = 24). The quality value of the research instrument was more a reliable than 0.80 (n = 21).The main parts of the research study involved in the relation between leadership and work engagement (n = 20).The secondary parts was followed by a prediction of leadership with work engagement (n = 8). Therefore, it is implied that the number of research type about leadership of Thai nurses and work engagement is minimal.